2007
DOI: 10.1203/pdr.0b013e3180a76dad
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY (3-36) Represents a High Percentage of Total PYY Immunoreactivity in Preterm and Full-Term Infants and Correlates Independently With Markers of Adiposity and Serum Ghrelin Concentrations

Abstract: ABSTRACT:The gut hormone peptide YY 3-36 ] has been suggested to posses anorexigenic actions in animals and human adults. However, its circulating concentrations and function have not been studied in neonates. Serum concentrations of PYY (3-36) were determined by RIA (RIA) in 62 healthy preterm infants [mean(SD) gestational age, 32.0(2.1) weeks; postnatal age, 40.9(14.8 d)] and 15 healthy fullterm infants of comparable postnatal age and gender. The correlations between PYY (3-36) levels and anthropometric char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…An epidemiological study has supported this by showing that rapid weight gain in infancy is associated with a higher fasting concentration of ghrelin, reflecting alterations in the appetite regulatory system ( 12 ) . The present results are also in accordance with previous studies of young children which showed that infants who were born with a low birth weight ( 13 ) or born preterm ( 13 , 28 , 29 ) had elevated levels of fasting PYY, reflecting greater satiety. The results from previous studies in which the association between birth weight and fasting levels of ghrelin has been investigated are conflicting, showing no differences ( 14 , 16 ) , decreased ( 13 ) or even elevated ( 15 , 17 ) ghrelin levels among children born with a low birth weight compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…An epidemiological study has supported this by showing that rapid weight gain in infancy is associated with a higher fasting concentration of ghrelin, reflecting alterations in the appetite regulatory system ( 12 ) . The present results are also in accordance with previous studies of young children which showed that infants who were born with a low birth weight ( 13 ) or born preterm ( 13 , 28 , 29 ) had elevated levels of fasting PYY, reflecting greater satiety. The results from previous studies in which the association between birth weight and fasting levels of ghrelin has been investigated are conflicting, showing no differences ( 14 , 16 ) , decreased ( 13 ) or even elevated ( 15 , 17 ) ghrelin levels among children born with a low birth weight compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…The minimum sample size of the study was calculated using our previous report of circulating ghrelin and PYY concentrations in healthy full-term infants [25]. Assuming an α risk of 0.05, a power of 0.80, and a bilateral test, it was estimated that approximately 10 neonates was the minimum number of infants needed in each group to detect a significant difference of one SD in mean ghrelin or PYY levels between infected and healthy infants.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Τα άνω και κάτω όρια του θηκογράμματος αντιπροσωπεύουν το εύρος τιμών. Η GLP-1 ανιχνεύεται στο αίμα του ανθρώπινου ομφάλιου λώρου στη γέννηση (396).…”
Section: A G a C A S E S Iu G R C A S E S Mbp Concentrations (Ngunclassified